An empirical examination of critical barriers in transitions between technology push and demand pull strategies in manufacturing organizations. Issue 3 (23rd April 2018) - Singla, Anuj; Sethi, APS; Ahuja, Inderpreet Singh
Abstract : Purpose: The purpose of this paper is to examine critical barriers in transitions between technology push (TP) and demand pull (DP) strategies in Indian manufacturing industries for accomplishing sustainable development. Design/methodology/approach: The factors that affect the transitions have been extracted and analyzed using factor analysis technique. For the purpose, various critical barriers are grouped together based on their relevance to TP-DP strategies. The responses to critical barriers have been collected from different Indian manufacturing organizations practicing TP-DP strategies, using a well-framed TP-DP questionnaire. Further, the responses are analyzed using factor analysis which improved the data interpretation. Findings: Four latent factors were extracted from critical barriers and revealed that the manufacturing organizations face these barriers in transitions between TP-DP strategies. The recognition of the outcomes of critical barriers has been perceived to be substantial in the present context. Originality/value: The research concludes that TP-DP strategies in Indian manufacturing industries encounter relevant critical barriers for accomplishing sustainable development. The outcomes of the study will help TP-DP practitioners, HR executives and organizational managers in manufacturing companies to develop clear understanding about the significant TP-DP strategies to be followed comprehensively for realization of sustainable development. The manufacturing organizations will be able to formulate and express their policies and issues in a more pertinent manner. Hence, the knowledge obtained from the empirical examination of critical barriers in transitions between TP and DP strategies will be helpful in improving the overall performance of manufacturing industries involved in the present study.